The effects of strikes on the share returns of gold and platinum mining companies - Tsotetsi, Oupa Jacob (Graduate School of Business (GSB), 2024)
South Africa is one of the world's leading mining and minerals-processing countries, accounting for 8.2% of gross domestic product (GDP). Labour strikes are a platform that enable workers to demonstrate their dissatisfaction towards their employer concerning labour relations issues. Mining strikes in South Africa date back to 1922 and continue to occur today. The occurrences of the Global Financial Crisis of 2007 to 2009, most recently the COVID-19 pandemic and loadshedding, among others,have exacerbated South Africa's historic challenges of poverty, unemployment and inequality resulting in increases in labour strikes. This study aims to assess the effects of strikes on the share returns of gold and platinum mining companies during the period of 2010 to 2022 using the event study methodology. Secondary data from IRESS, Websites of selected mining companies and the SENS information, the annual industrial action report, newspaper articles and news feeds were used to achieve the articles' empirical analysis. A 61-day event window is used, including 30 days before and 30 days after the announcement of the strike. The effects of the announcement, settlement and duration of astrike on the share returns is tested, as well as whether the effects vary depending on whether the strikes are protected orunprotected, and for gold versus platinum mining companies. Significant negative cumulative average abnormal returns (CAARs) wereobserved during the periods of the announcement of the strike and positive returns around the settlement of the strike. The announcement CAARs for both protected and unprotected strikes were negative, meaning a decline in the share return, while the settlement results showed an increase in share return for both. The gold versus the platinum mining strikes showed a negative effect on the share return irrespective of the industry. The longer-duration strikes had a greater effect on the share return compared to the shorter-duration strikes. Based on the empirical findings, it can be concluded that strike action has a negative effect on the share returns of South African gold and platinum mining firms. The key contributions of the studyare to bridge the gap in financial markets' understanding of the effects of strikeson the share return of gold and platinum companies and the need to integrated collective bargaining to avert strikes or reduce the duration of strikes, thereby increasing investors' confidence